Wire Drag Operations using Raydist "T" - Walter, Merritt N. (The International Hydrographic Review, 2015)
This paper describes a two-month wire drag project using Raydist "T" , a new passive form of the Raydist radiolocation system. Operations were conducted in the lower Chesapeake Bay by the Rude and Heck, wire drag vessels of the National Ocean Survey (NOS) (formerly U.S. Coast and Geodetic Survey). Raydist DR-S has been in regular use by the Rude and Heck for nearly four years. The only modifications required to convert existing DR-S shipboard installations for Raydist "T" operations were accomplished by module substitution in the DR-S Navigators. Shipboard CW transmitters, needed for range-range operation, were not employed. The ground network and shipboard equipment are described, and the method of conducting wire drag operations using Raydist "T" is discussed. Results of the two-month project are presented, along with a comparison of the operational and performance characteristics of Raydist "T" with those of the range-range and 3-station hyperbolic forms of Raydist.